One day hero. Jules Reboux at the crucible of prehistory in 1860s Paris - Schlanger, Nathan (Complutum, 2013)
The historiography of prehistoric archaeology, smoothly leading from the establishment of human antiquity by Boucher de Perthes in the late 1850s to the disciplinary and classificatory framework set up by Gabriel de Mortillet in the 1870s, still leaves considerable gaps in our understanding of the practical and conceptual developments of the field. The forgotten figure of the amateur Jules Reboux, who explored from the mid 1860s to the mid 1870s the quarry sites of Levallois, on the northern outskirts of Paris, proves in this respect salutary. Given the nature and scope of the controversies he raised, understanding Reboux’s various claims should help us reach beyond the usual front-rankers and the scripted scenarios. With his terminological and graphic innovations, Reboux’s contribution to nineteenth-century prehistoric archaeology was in fact quite fundamental, touching on such paradigmatic issues as the recognition of stratigraphic superposition, the study of stone implement manufacture and use, and the recourse to implement types for chronological classification.